Pressmud Compost for Improved Nitrogen and Phosphorus Content Employing Bacillus Strains - Uzma Sajid; Sumaira Aslam; Ali Hussain; Tamseela Mumtaz; Safina Kousar (Recycling)
Pressmud, a by-product of sugarcane processing, is typically disposed of through incineration or landfilling, though it has considerable potential in organic agriculture. This study explored the composting of pressmud through bioaugmentation using specific bacterial strains. Two experimental setups were created: E2 with a cellulolytic and phosphorus-solubilizing strain, Bacillus amyloliquefaciens-ASK11, and E3 with a nitrogen-fixing strain, Bacillus megaterium-ASNF3. A control setup (E1) was also maintained without bacterial augmentation. Results indicated that the Bacillus-enhanced composts in E2 and E3 showed significant increases of 129% and 83% in nitrogen and of 49% and 91% in phosphorus contents, respectively, after 60 days. Additionally, organic matter decomposition improved by 49–50% in the bioaugmented setups after 60 days. FTIR analysis revealed organic phosphate peaks and P-O-C stretching bands at 1025 cm−1 in the E2 compost, while a nitrogen vibration band at 3849 cm−1 in E3 indicated significantly higher nitrogen content compared to the control. The Bacillus-enriched pressmud compost not only accelerated the composting process but also enhanced nutrient levels, positioning it as a promising biofertilizer for rehabilitating barren lands.